Therapeutic Effect and Cost-Benefit Analysis of Three Different Nutritional Schemes for Esophageal Cancer Patients in the Early Post-operative Period - Huang, Chen; Liang, Xinyu; Du, Shanshan; He, Jie; Bai, Qian; Feng, Xiaoqing; Liu, Xiaoqing; Tian, Xu; Wang, Jian (Frontiers in Nutrition, 2021)
Objective: To retrospectively investigate the comparative efficacy, safety and cost-benefits of three nutritional treatment schemes including short peptide jejunal nutrition (SPJN), whole protein jejunal nutrition (WPJN), and partial parenteral nutrition (PPN) in patients underwent esophagectomy for esophageal cancer in our hospital. This study was carried out in accordance with the conceptual framework of nutritional therapy in fast-track rehabilitation surgery. Methods: We retrospectively reviewed 305 esophageal cancer patients who received esophagectomy. The sample was divided into short peptide jejunal nutrition (SPJN) treatment group [SPJN group, n=98 (32.1%)], whole protein jejunal nutrition (WPJN) treatment group [WPJN, n=95 (31.1%)] and total parenteral nutrition (PPN) treatment group (PPN group, n=112 (36.7%)]. The differences of the serum total protein (TP), albumin (ALB), prealbumin (PA), hemoglobin (HGB), white blood cells (WBCs), red blood cells (RBCs) and neutrophils were compared among 3 groups. We also investigated the relationship of the fluid intake, urine output, gastric juice drainage volume and thoracic drainage volume among 3 groups at 3 days after operation. Moreover, the differences of cost-benefit indexes, complications, hospital stay and hospital expenditure were also analyzed. Results: The serum TP, ALB and PA in the SPJN group were considerably higher than those in the WPJN group and PPN group (p<0.05). There were significantly less gastrointestinal decompression drainage fluid and thoracic drainage fluid in the SPJN group than in the WPJN group (p<0.05). Besides, the hospital stay and postoperative hospital stay were obviously shorter and the incidence rate of anastomotic leakage, infection, gastrointestinal reaction, were remarkably lower in the SPJN group than in the WPJN group (p<0.05). Moreover, patients in the PPN group spent notably less money on hospitalization than those in the SPJN group (p<0.001) and the WPJN group (p<0.001). Conclusion: Patients may obtain benefits in improving protein after receiving SPJN at the early stage after esophagectomy. Meanwhile, patients may obtain benefits in improving postoperative complications and hospital stay after receiving SPJN or PPN. However, the difference between SPJN and PPN require further study because of no difference was detected for clinical outcomes. In addition, postoperative fluid control and the selection of appropriate jejunal nutrition require further attention.